2019
DOI: 10.1016/j.molmet.2019.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Programmed increases in LXRα induced by paternal alcohol use enhance offspring metabolic adaptation to high-fat diet induced obesity

Abstract: ObjectivesPaternally inherited alterations in epigenetic programming are emerging as relevant factors in numerous disease states, including the growth and metabolic defects observed in fetal alcohol spectrum disorders. In rodents, chronic paternal alcohol use induces fetal growth restriction, as well as sex-specific alterations in insulin signaling and lipid homeostasis in the offspring. Based on previous studies, we hypothesized that the observed metabolic irregularities are the consequence of paternally inhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 44 publications
(75 reference statements)
0
22
1
Order By: Relevance
“…During these experiments, we utilized a well-established breeder diet, to which dams had unrestricted access and subjected the mice to minimal handling stress. We did not observe cannibalism in any of our previous postnatal studies examining the offspring of alcohol-exposed sires [ 10 , 11 ], or in the Control-FA treatment group, indicating the strong possibility that these outcomes were associated with the treatments. After 30 days of postnatal growth, we terminated the experiments due to the low number of surviving offspring ( Fig.…”
Section: Resultsmentioning
confidence: 52%
“…During these experiments, we utilized a well-established breeder diet, to which dams had unrestricted access and subjected the mice to minimal handling stress. We did not observe cannibalism in any of our previous postnatal studies examining the offspring of alcohol-exposed sires [ 10 , 11 ], or in the Control-FA treatment group, indicating the strong possibility that these outcomes were associated with the treatments. After 30 days of postnatal growth, we terminated the experiments due to the low number of surviving offspring ( Fig.…”
Section: Resultsmentioning
confidence: 52%
“…Paternally inherited alterations in epigenetic programming were also shown to be related to metabolic defects observed in foetal alcohol spectrum disorders. In rodents, chronic paternal alcohol use affected insulin signaling and lipid homeostasis in the offspring through paternally inherited alterations in liver × receptor activity ( Chang et al, 2019a ). Similar findings were reported by Chang et al (2019b) , assessing long-term impacts of chronic preconception paternal alcohol use in mice.…”
Section: Discussionmentioning
confidence: 99%
“…In another study examining parental binge alcohol abuse, differences in the expression of genes involved in neurogenesis, reproductive function, and regulation of obesity were observed in offspring ( Przybycien-Szymanska et al, 2014 ). Also, the studies of Chang et al (2019a) and Chang et al (2019b) using a mouse model of paternal alcohol exposure have identified the markers of hepatic fibrosis and abnormalities in both lipid production and insulin signaling in the offspring of alcohol-exposed sires. The aforementioned studies raise the possibility that alcohol affects naïve offspring even in the absence of direct foetal alcohol exposure, and epigenetic inheritance may be the mechanism responsible for this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…We washed cells twice with PBS containing protease inhibitor cocktail (Cat# 78437; Thermo Scientific) and re-suspended them in medium (DMEM F-12 Cat# 11320-033; Invitrogen) containing 0.1 volume crosslinking solution [ 33 ]. We carried out chromatin immunoprecipitation reactions following the previously published protocol [ 34 ]. The specific antibodies used in this study include anti-H3K9me2 (Cat# 39239; Active Motif, RRID:AB_2793199), antiH3K9me3 (Cat# 05-1242; Millipore-Sigma, RRID:AB_1587136), antiH4K20me3 (Cat# 91107; Active Motif, RRID:AB_2793777), anti-SATB2 (Cat# ab34735; Abcam, RRID:AB_2301417) and the negative IgG control (Cat# SC-2027; Santa Cruz, RRID:AB_737197).…”
Section: Methodsmentioning
confidence: 99%